Dampak Program Unggulan Madrasah Dalam Pengembangan Karakter Siswa Di Madrasah Aliyah Negeri 1 Palembang - Emilia Agustini; Abdullah Idi; Didi Suhendi (Jurnal Empirika, 2018)
This research was conducted at MAN 1 Palembang, located on Jl. Governor H. Bastari (Jl. Pendidikan) Jakabaring Palembang. The purpose of the research was to analyze the impact of the excellent program in the development of student character at Madrasah Aliyah Negeri 1 Palembang. The research was conducted using a qualitative method. In obtaining data using in-depth interviews and participatory observation consisting of 12 informants and observers. The theory of Petter L Berger's socialization process is used as a research analysis tool to see and analyze the ongoing socialization process in an excellent programs of Madrasah. The results of this research that through the excellent program of Madrasah which includes excellent academic programs, excellent tahfidz programs and excellent journalistic programs have a good impact on student character development. The character values of students that increase are: (1) Religious, (2) Discipline, (3) Hard Work, (4) Creative, (5) Independent, (6) Curiosity, (7) Communicative, ( 8) Respect for achievement, (9) Communicative, (10) Responsibility. From the results of the research illustrate that there is a development of student character that manifested in the form of reduced delinquency of order that doing by students after the existence of excellent programs of Madrasah.